Knowledge, Attitude and Practices towards COVID-19 among Medical Students (Journal of KIST Medical College, 2020)
Introduction: In late December 2019, COVID-19 was first seen in Wuhan, China which has been spreading to the whole world in subsequent months. Till the time this manuscript is written, COVID-19 has infected more than 2million people and killed more than 129843 people all around the world. First step in fighting against COVID-19 is to have appropriate knowledge and correct attitude and practices.Methods: This study was done to know the knowledge, attitude and practices on COVID-19 amongst medical students of Kathmandu University School of Medical Sciences (KUSMS) using internet based structured questionnaires. The survey was conducted from April 2, 2020 to April 09, 2020 (one-week after lock down following COVID-19 spread in Nepal). Structured questionnaire was used by the Medical students of Kathmandu University Hospital. There were 19 questionnaires regarding Knowledge, three regarding Attitude and five regarding Practices.Results: Out of 631 responders, the mean correct Knowledge score was 83.4%. Of the 19 Knowledge questionnaires, the mean score was 15.8 (Range 0-19). Regarding the Attitude questionnaire, 81.7% responders had a positive attitude toward COVID-19 being controlled globally in near future. Majority of the responders wore masks when going out in recent days (96%) and 97.6% of responders didn’t go to crowded places during this period.Conclusion: Medical Students have good knowledge, optimistic attitude and appropriate preventive practices towards COVID-19. Better knowledge is associated with online or onsite training obtained about COVID-19 outbreaks. Optimistic Attitude and appropriate preventive practices was associated with better knowledge of the responders.